Structural controls on the Bonsucesso Zinc-Lead Deposit, Vazante Group, Brazil - Ferraz, Edson Ricardo Maia [UNESP]; Luvizotto, George Luiz [UNESP]; Okubo, Juliana [UNESP]; Batiston, Denis Antonio [UNESP] (FapUNIFESP (SciELO), 2023)
The Bonsucesso zinc-lead (Zn-Pb) sulfide deposit is hosted in carbonate rocks from the Vazante Group (transition of the Mesoproterozoic to the Neoproterozoic time), northwest of Minas Gerais State, Brazil. Regional deformation is associated with the thin-skinned tectonics that led to the formation of the foreland zone of the Brasília Orogen during the Neoproterozoic. These orogenic processes are the trigger of Zn-Pb mineralization in many base-metal deposits in the Vazante Group. Here, we describe the ore textures and the structures of the deposit to define its structural controls in deposit scale and formulate hypotheses about its forming process in the context of other Vazante Zn-Pb deposits. Mineralization distribution is controlled by a high-angle fault zone striking NNW and dipping 60° to WSW. Fault-related fractures functioned as pathways for Zn-Pb-rich fluids to be redistributed and crystallize where chemical conditions were adequate. Mineralization was likely formed in an extensional setting in breccia zones controlled by flexurally induced normal faults related to development of the foreland basin of Brasília Orogen. Later, the entire Vazante sequence underwent an inversion process and extensional structures were reactivated or obliterated. Finally, an understanding of local controls may be of good use to target exploration for new orebodies in the district scale.
Keywords: Brasília Belt; Morro do Calcário Formation; MVT; structural geology; zinc